Deteksi Bakteri Coliform pada Es Batu yang Disajikan di Tempat Makan Tenda di Kecamatan Grogol Petamburan - Chrysilla Dita; Donna Mesina Pasaribu; Nicolas Layanto (Jurnal Kedokteran Meditek, 2020)
Bacteria contamination in ice cube may come from poor hygiene process including dirty ice cube maker appliances and the use of unclean water. According to the Indonesian government regulation (BPOM RI No. 16 of 2016 about microbiology criteria for processed food), the standard for Escherichia coli and coliform bacteria content in drinking water is 0/250ml. Grogol Petamburan area is a location where most students of the Faculty of Medicine Ukrida live, therefore the author was interested to do this research. This study aimed to detect the presence of coliform bacteria in ice cube sold by street food vendors. This study used an observational descriptive study method. Ice cube samples were obtained from 10 street vendors in Grogol Petamburan area. Samples were tested based on TPC and MPN methods to detect coliform bacteria. Results showed that coliform bacteria and fecal coliform were detected in all ice cube samples. It can be concluded that all ice samples are not good for consumption according to the microbiological requirements.